2004
DOI: 10.1093/glycob/cwh072
|View full text |Cite
|
Sign up to set email alerts
|

Physical interactions between the Alg1, Alg2, and Alg11 mannosyltransferases of the endoplasmic reticulum

Abstract: The early steps of N-linked glycosylation involve the synthesis of a lipid-linked oligosaccharide, Glc(3)Man(9)GlcNAc(2)-PP-dolichol, on the endoplasmic reticulum (ER) membrane. Prior to its lumenal translocation and transfer to nascent glycoproteins, mannosylation of Man(5)GlcNAc(2)-PP-dolichol is catalyzed by the Alg1, Alg2, and Alg11 mannosyltransferases. We provide evidence for a physical interaction between these proteins. Using a combination of biochemical and genetic assays, two distinct complexes that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 29 publications
3
59
0
Order By: Relevance
“…3A), suggesting stronger interaction of hAlg1p with itself than with hAlg2p or hAlg11p. Furthermore, this observation is completely in accordance with physical interactions among yeast Alg1p, Alg2p, and Alg11p, which were detected with our co-immunoprecipitation experiments (20). Taken together, we found that these mannosyltransferases can associate with each other to form an MT complex that includes hAlg1p, hAlg2p, and hAlg11p in a ratio of 2:1:1, respectively.…”
Section: C-1 Halg7p Halg14p and Halg13p Form A Gpt/nagt Complexsupporting
confidence: 90%
“…3A), suggesting stronger interaction of hAlg1p with itself than with hAlg2p or hAlg11p. Furthermore, this observation is completely in accordance with physical interactions among yeast Alg1p, Alg2p, and Alg11p, which were detected with our co-immunoprecipitation experiments (20). Taken together, we found that these mannosyltransferases can associate with each other to form an MT complex that includes hAlg1p, hAlg2p, and hAlg11p in a ratio of 2:1:1, respectively.…”
Section: C-1 Halg7p Halg14p and Halg13p Form A Gpt/nagt Complexsupporting
confidence: 90%
“…Recently, a number of other ER glycosyltransferases, namely Alg1, Alg2 and Alg11, which catalyze several steps of LLO biosynthesis on the cytosolic face of the ER have been shown to interact as hetero-oligomeric complexes that are important for their glycosyltransferase activity (32). We have not determined the stoichiometry of Alg13 and Alg14 within the hetero-oligomer nor have we ruled out the possibility that there may be additional interactions between Alg13 and Alg14with these or other ER proteins that may modify the activity of the UDP-GlcNAc transferase activity.…”
Section: Discussionmentioning
confidence: 99%
“…The lipid-linked GlcNAc 2 Man 3 pentasaccharide serves as substrate for Alg11p that elongates the LLO by two a-1,2-linked Man residues (Cipollo et al 2001;O'Reilly et al 2006). Interestingly, the three cytoplasm-oriented mannosyltransferases also form a hetero-oligomeric complex (Gao et al 2004). This results in two biosynthetic platforms that are characterized by the nucleotide-activated sugar substrate: the UDP-GlcNAc utilizing Alg7p/Alg13p/Alg14p and the GDP-Man-dependent Alg1p/Alg2p/Alg11p complex.…”
Section: Initial Steps Of Llo Biosynthesis On the Cytoplasmic Side Ofmentioning
confidence: 99%